A conceptual model of continuous improvement in total quality management from Islamic perspective - Afrin, Afroza Bulbul; Islam, Rafikul (Australian Academy of Business Leadership, 2018)
Continuous improvement (CI), one of the vital principles of total quality management (TQM), is now being practiced in almost every organization regardless their natures, shapes, and sizes. After developing the concept of CI in 1930s, Muslims are using the models and approaches developed by the non-Muslim scholars based on their own cultures and beliefs. The main purpose of conducting this particular study is to develop a new model of CI in TQM from Islamic perspective. After an extensive literature review, the researchers have developed a conceptual model of CI in TQM from Islamic perspective which is named as NAMS Cycle (initial letters of the components) where the main components are al-nīyah bil ikhlas, amal, muhāsaba and shukr. All of these components also consist of some other constructs. Both the Muslim and non-Muslim believers will be benefited from this research if they have good faith in the Creator and the Day of Judgment.